Effect of the Hearth Program on Stunting Prevention Behavior - Sambriong, Maria; Kuncoro, Amin; Manek, Daniel (Journal of Economics and Public Health, 2022)
The research aims to analyze the effecttof the hearthhprogrammon maternal behaviorrin preventing stunting. Ethics clearance has been received from the Ethics Committee in Kupang. This study used a pre-experimental method with a one-group pretest-posttest design. The sample consisted of thirty people who were randomly selected. They are toddlers who live with their parents in Kuanheun Village. Stunting prevention behavior was obtained through interviews using a questionnaire. The children's weight and height were measured before and after the hearth program. This activity is carried out twice for three months by involving all participants. Data analysis used a paired t-test. The research showed that the hearth program had an effect on the mother's behavior. This study has not fully implemented the positive deviance approach. It will be better to applied for the next program. So the researchers can use this method with a better initial investigation and involve the community and all community leaders.